Cercarial glycocalyx of Schistosoma mansoni activates human complement. - Samuelson, J C (1986)
Human complement activation by cercariae and schistosomula of the human parasite Schistosoma mansoni was studied in vitro. Cercariae are composed of tails which are shed after infection of the host and bodies which transform into the larvae or schistosomula after infection. After incubation in fresh normal human serum (NHS), cercarial tails bound more anti-C3 antibodies than did cercarial bodies (CB), and the tails were rapidly lysed, while the attached CB remained intact. Complement activation by cercariae was dependent on the alternative pathway but was independent of antibody, as shown by C3 deposition by hypogammaglobulinemic human sera. By transmission microscopy, the fibrillar glycocalyx on both CB and tails was stained by NHS but not by heat-inactivated serum (HI-NHS). The glycocalyx was labeled with periodate and tritiated borohydride, and parasites were incubated in NHS and HI-NHS. After solubilization, the labeled glycocalyx on organisms incubated in NHS but not HI-NHS bound anti-C3 antibodies. Of the CB incubated with eserine sulfate to prevent transformation, 78% +/- 10% were dead after culture for 24 h in NHS. In contrast, 21% +/- 12% of the CB were dead after culture in HI-NHS. Schistosomula incubated in NHS bound 37% of the amount of anti-C3 antibodies bound by cercariae but were not killed by NHS. In conclusion, the cercarial glycocalyx activated human complement, and schistosomula were less susceptible to killing than cercariae because they had less glycocalyx and activated less complement.